2022
DOI: 10.2174/1573405616666201231095918
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Assessment of Radial Scars/complex Sclerosing Lesions of the Breast

Abstract: Purpose: To describe the magnetic resonance characteristics of radial scars/complex sclerosing lesions (RS/CSL) of the breast using the current BI-RADS lexicon. To investigate the value of diffusion weighted imaging to predict malignancy. Patients and methods: From 2010 to 2017 we have found 25 women with architectural distortion at mammography who underwent surgical resection with a final hystopathologic report of RS/CSL. For description of MRI findings we adhered to BI-RADS classification (5th edition). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…One approach to the stratification of risk conferred by these high-risk lesions has been the study of imaging features on MRI, as many of these lesions are diagnosed by this modality. Some authors have reported modestly increased risk of upgrade with ALH, LCIS, CSL and IPA lesions that are large in size, have clumped non-mass enhancement (NME) with mixed kinetics or NME with regional/segmental distribution [ 29 , 30 , 31 ]. Other authors have not found any imaging features predictive of upgrade.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to the stratification of risk conferred by these high-risk lesions has been the study of imaging features on MRI, as many of these lesions are diagnosed by this modality. Some authors have reported modestly increased risk of upgrade with ALH, LCIS, CSL and IPA lesions that are large in size, have clumped non-mass enhancement (NME) with mixed kinetics or NME with regional/segmental distribution [ 29 , 30 , 31 ]. Other authors have not found any imaging features predictive of upgrade.…”
Section: Discussionmentioning
confidence: 99%